Musculoskeletal Ultrasound Study Group in Collegio Reumatologi Italiani: workup activity - C. Venditti; V. Bruner (Verduci Editore, 2024)
The Collegio Reumatologi Italiani (C.Re.I.) Ultrasound Study Group aims to spread musculoskeletal ultrasound technique at every level across the Italian rheumatologists. The study group promoted a national survey on the diffusion of ultrasound (US) among members. This survey demonstrates a large diffusion of trained sonographers and ultrasound machines at all the clinical levels. When trained sonographers or ultrasound machines are not available, rheumatologists prefer to refer patients to others experienced rheumatologists. During the last two C.Re.I. National Congresses, the Ultrasound Study Group opened a working table to delineate future skills improvement, ranging from theoretical lessons to the assessment of difficult clinical cases, in order to consolidate ultrasound use during diagnostic and therapeutic processes. The objectives of the Ultrasound Working Table are the starting point for consolidation and diffusion of rheumatological ultrasound in the rheumatological clinical routine procedure. The aim of this report is to divulgate the Study group's initiatives and achieved objectives.